2020
DOI: 10.3389/fendo.2020.00433
|View full text |Cite
|
Sign up to set email alerts
|

Rare Germline DICER1 Variants in Pediatric Patients With Cushing's Disease: What Is Their Role?

Abstract: Context: The DICER1 syndrome is a multiple neoplasia disorder caused by germline mutations in the DICER1 gene. In DICER1 patients, aggressive congenital pituitary tumors lead to neonatal Cushing's disease (CD). The role of DICER1 in other corticotropinomas, however, remains unknown. Objective: To perform a comprehensive screening for DICER1 variants in a large cohort of CD patients, and to analyze their possible contribution to the phenotype. Design, setting, patients, and interventions: We included 192 CD cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Several reports have probed the relation between DICER1 and carcinogenesis (4). LOH as well as a second somatic mutation in the RNase III domain in DICER1 is regularly observed in pituitary blastoma (46). However, its impact on pituitary tumourigenesis needs further research although Cotton et al (47) described a 50-year-old female with a microprolactinoma caused by a DICER1 alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have probed the relation between DICER1 and carcinogenesis (4). LOH as well as a second somatic mutation in the RNase III domain in DICER1 is regularly observed in pituitary blastoma (46). However, its impact on pituitary tumourigenesis needs further research although Cotton et al (47) described a 50-year-old female with a microprolactinoma caused by a DICER1 alteration.…”
Section: Discussionmentioning
confidence: 99%
“…As germline mutations, MEN1, PRKAR1A, CDKN1B , and AIP genes should be considered as a young age-onset genetic syndrome phenotype ( 64 ). In aggressive pediatric Cushing’s syndrome, the DICER1 gene has been reportedly identified to have a causal role in ACTH-producing pituitary blastoma caused by DICER1 syndrome ( 65 67 ) ( Table 1 ). Since DICER1 is an enzyme required for the cleavage of a precursor into mature microRNA, noncoding RNA, including microRNA, are associated with the pathogenesis of pituitary ACTH-producing tumors and their aggressiveness.…”
Section: Molecular Pathologymentioning
confidence: 99%
“…In children, temozolomide treatment for aggressive pituitary adenoma and carcinoma is quite rare, which leads to insufficient treatment data. In limited cases of DICER1 mutations with ACTH-secreting pituitary tumors, the effect of temozolomide has not been clearly shown ( 65 , 124 ). Although there is no established course of treatment because of the paucity of data, the ESE guidelines suggest that temozolomide might be beneficial in adults ( 88 ).…”
Section: Treatmentmentioning
confidence: 99%
“…The main clinical presentations of neonates are pressure symptoms due to the large tumor and signs and symptoms of Cushing's disease, with high mortality [74]. A recent screening for DICER1 variants in a large cohort of Cushing's disease patients demonstrated that DICER1 gene variants may contribute to the pathogenesis of nonsyndromic corticotropinomas [75].…”
Section: Prkar1amentioning
confidence: 99%